Habitat disturbance and small mammal richness and diversity in an Atlantic rainforest area in southeastern Brazil - Vera y Conde,C. F. (2006)
Since disturbance is an important ecological factor affecting species diversity in natural environments, the increasing human occupation rate in Brazilian Atlantic rainforest, which supports about 50% of Brazil's human population, has resulted in intense habitat degradation and fragmentation. Within this rainforest, animal and plant species have been lost at a high rate, and biological and diversity is presently vulnerable. Various animals community studies along a gradient of environmental disturbances have shown that the highest species diversities occur in habitats with intermediate levels of disturbance frequency and intensity. In the present study, which was carried out in the Atlantic forest of Ilha Grande (23° 11' S and 44° 12' W), an island located on the southern coast of Rio de Janeiro State, southeastern Brazil, we estimated species richness, diversity, and abundance of small mammals in three forest areas having different disturbance levels. This was done, in each of these areas and in an anthropic area that they surround, by establishing trails 200 m long, in which points were marked at 20 m intervals. The work involved a total effort of 4800 trap/nights. We also measured some habitat variables at each site in order to evaluated their disturbance levels. Our data showed that the two most conserved forests had the lower species richness and small mammal diversity, while in the anthropic area wild species were absent. The forest with an intermediary level of disturbance showed higher values for species richness and diversity, with the anthropic area presenting the highest disturbance level.